“And I Believe in Signs”: Soviet Secularity and Islamic Tradition in Kyrgyzstan - Boron, Usmon (Comparative studies in society and history, 2024)
In Central Asia, the Soviet state had destroyed most Islamic institutions by the late 1930s, which gradually alienated millions of Soviet Muslims from the basics of Islamic theology and key Islamic practices of virtue cultivation, including the five daily prayers (namaz), Islamic ethics of dressing (like covering certain parts of the body), and certain lifestyle prescriptions (such as the avoidance of alcohol, gambling, and premarital sex). As a result, mainstream Islam in Central Asia came to revolve around the main Islamic life-cycle rites (i.e., male circumcision, the marriage ceremony, and funeral prayer) and occasional practices of uttering blessings, reciting short Qur’anic verses for the souls of the deceased, and visiting shrines, among others. Although more than thirty years have passed since the fall of the USSR, this non-observant form of Islam remains widespread in the region. Inquiring into the conceptual and affective aspects of Soviet forced secularization in Central Asia, I make two interrelated interventions into secularism studies and the anthropology of Islam. First, I theorize Soviet secularism through attending to the modern state’s aspiration to transcend and transform the particularities of lived traditions, which reveals significant overlaps between communist and liberal modes of statecraft and subject formation. Second, reflecting on a non-observant form of Islam in contemporary Kyrgyzstan, I ask: what remains of a tradition of virtue ethics when its modes of abstract reasoning and virtue cultivation have all but vanished?